2020
DOI: 10.1136/neurintsurg-2019-015026
|View full text |Cite
|
Sign up to set email alerts
|

The evidentiary basis of vertebral augmentation: a 2019 update

Abstract: No aspect of neurointerventional practice has been associated with as longstanding contention and debate as to its effectiveness as has vertebroplasty (VP). Four blinded randomized controlled trials published since 2009 have demonstrated conflicting results regarding a conferred benefit in pain reduction and functional improvement for patients who undergo VP for osteoporotic vertebral compression fractures. Significant heterogeneity exists between each of these trials, which has resulted in difficulty for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…After the publication of randomized studies in 2009 showing no superiority of VA over a sham procedure [7,8], several studies disputing the beneficial effects of VA have been reported. Debate and widespread concern have also been raised regarding the design and execution of these studies [49]. In 2018, the ASBMR Task Force Report stated that because the role of VA in both acute and chronic fractures has been controversial, the routine use of VA is not supported by current evidence.…”
Section: Vertebral Augmentationmentioning
confidence: 99%
“…After the publication of randomized studies in 2009 showing no superiority of VA over a sham procedure [7,8], several studies disputing the beneficial effects of VA have been reported. Debate and widespread concern have also been raised regarding the design and execution of these studies [49]. In 2018, the ASBMR Task Force Report stated that because the role of VA in both acute and chronic fractures has been controversial, the routine use of VA is not supported by current evidence.…”
Section: Vertebral Augmentationmentioning
confidence: 99%
“…Chandra et al (49) reviewed the evidence including the recommendations of national societies and professional organizations. De Leacy et al (84) expanded that analysis to include the burgeoning literature on mortality in compression fracture patients.…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%
“…[3][4][5] Review of 10 RCTs comprising 1,098 patients demonstrated 16 procedure-related complications for a rate of 1.5%, and only two of those complications were considered serious adverse events (SAEs). 50 NSM also carries risks, such as long-term analgesic use and the associated side effects. VA was shown to reduce the analgesic requirement in 91% of patients.…”
Section: Expected Outcomesmentioning
confidence: 99%